Histological analysis of the medial gastrocnemius muscle in young healthy children - Andries, Anke; Deschrevel, Jorieke; Maes, Karen; De Beukelaer, Nathalie; Corvelyn, Marlies; Staut, Lauraine; De Houwer, Hannah; Costamagna, Domiziana; Nijs, Stefaan; Metsemakers, Willem-Jan; Nijs, Elga; Hens, Greet; et al. (Frontiers in Physiology, 2024)
Introduction: Histological data on muscle fiber size and proportion in (very) young typically developing (TD) children is not well documented and data on capillarization and satellite cell content are also lacking.Aims: This study investigated the microscopic properties of the medial gastrocnemius muscle in growing TD children, grouped according to age and gender to provide normal reference values in healthy children. Methods: Microbiopsies of the medial gastrocnemius (MG) muscle were collected in 46 TD boys and girls aged 2-10yr subdivided into 4 age groups (2-4, 4-6, 6-8 and8-10yr).Sections were immunostained to assess fiber type cross-sectional area (fCSA) and proportion, the number of satellite cells (SC), capillary to fiber ratio (C/F), capillary density for type I and II fiber (CFD), capillary domain and heterogeneity index. fCSA was normalized to fibula length² and the coefficient of variation (CV) was calculated to reflect fCSA intrasubject variability. Results: Absolute fCSA of all fibers increased with age (r=0. 7267, p<0.001) but more in boys (+112%, p<0.05) than in girls (+48%, p>0.05) in whom the fCSA was larger at young age. Normalized fCSA, CV and fiber proportion did not differ between age groups and gender. C/F was strongly correlated with age in boys (r= 0.83, p<0.001), and to a lesser extent in girls (r=0.37, p=0.115), while other capillary parameters as well as the number of SC remained stable with increasing age in boys and girls. Discussion: This study provides reference values of histological measures in MG according to age in normally growing boys and girls. These data may be used as a reference to determine disease impact and efficacy of therapeutic approach on the muscle.